Effect of GA₃ Soaking Duration on Germination of Robusta Coffee Seeds - Mela Rahmah; Syafrison; Lela Febriani Ariska (Jurusan Budidaya Perkebunan, 2026)
Robusta coffee seeds (Coffea canephora) exhibit relatively long physiological dormancy, which often constrains seedling production. One approach to accelerate seed germination is soaking seeds in gibberellic acid (GA₃). This study aimed to evaluate the effect of GA₃ soaking duration at 250 ppm on germination and early seedling growth of robusta coffee seeds. The experiment was arranged in a Completely Randomized Design (CRD) with a single factor, namely GA₃ soaking duration, consisting of five levels: 0, 12, 24, 36, and 48 hours. Observed parameters included time to dormancy breaking, germination percentage, root length, hypocotyl length, percentage of cotyledon opening, and fresh weight of seedlings. Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) at the 5% significance level. The results showed that GA₃ soaking duration significantly affected dormancy-breaking time, germination percentage, root length, hypocotyl length, and seedling fresh weight, but had no significant effect on cotyledon-opening percentage. Soaking seeds in a GA₃ solution (250 ppm) for 24–36 hours produced the best response, as indicated by faster dormancy-breaking, higher germination percentage, and better early seedling growth. Excessive soaking duration tended to reduce treatment effectiveness. Therefore, an appropriate GA₃ soaking duration is recommended to improve robusta coffee seedling establishment.